Association between family factors and 24-h movement behaviors of adolescents—a cross-sectional study of Chinese high school students - Fan, Huiying; Fan, Guoqiang; Meng, Jie (Frontiers in Public Health, 2025)
BackgroundFamilies have a significant effect on the patterns of physical activity exhibited by adolescents, and they influence the movement behaviors of adolescents through both direct and indirect roles. The aim of this study was to examine the association between meeting the 24-h movement guidelines and family factors.MethodsA total of 1,250 students (mean age16.1 ± 0.9 years; 48.2% were boys.) were selected from the 10th, 11th, and 12th grades in four urban and four suburban districts in Shanghai, China. The study used generalized linear models to assess the association between adherence to the 24-h movement behaviors and family factors, while adjusting gender, ethnicity, age, weight status, live in school. For statistical significance, p value <0.05 was used.ResultsAdolescents in nuclear families (OR = 1.273, CI = 0.031–0.451, p = 0.024), with no siblings (OR = 1.108, CI = 0.033–0.173, p = 0.004), middle (OR = 1.106, CI = 0.018–0.183, p = 0.017), and high SES (OR = 1.160, CI = 0.055–0.242, p = 0.002) were more likely to meet the 24-h movement behavior guidelines. For boys, middle (OR = 1.221, CI = 0.071–0.329, p = 0.002) and high (OR = 1.289, CI = 0.107–0.399, p = 0.001) SES were more likely to meet the 24-h movement behavior guidelines. Girls with nuclear families (OR = 1.488, CI = 0.121–0.674, p = 0.005) and no siblings (OR = 1.125, CI = 0.029–0.207, p = 0.009) were more likely to meet the 24-h movement behavior guidelines.ConclusionThis study demonstrated the role of family structure, having siblings, and SES in predicting adolescent 24-h movement behavior. The findings of the research assistance in providing information family factors for future interventions aimed at establishing adolescent 24-h movement behaviors. The mechanisms by which these family factors influence 24-h movement behavior should be explored in future, and the specific pathways by which family factors influence adolescent 24-h movement behavior should be clarified, in order to provide a more targeted theoretical basis for interventions.